2020
DOI: 10.1161/atvbaha.119.313885
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Recurrent COL5A1 Genetic Variant Is Associated With a Dysplasia-Associated Arterial Disease Exhibiting Dissections and Fibromuscular Dysplasia

Abstract: Objective: While rare variants in the COL5A1 gene have been associated with classical Ehlers-Danlos syndrome and rarely with arterial dissections, recurrent variants in COL5A1 underlying a systemic arteriopathy have not been described. Monogenic forms of multifocal fibromuscular dysplasia (mFMD) have not been previously defined. Approach and Results: We st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 61 publications
3
37
0
1
Order By: Relevance
“…Similar to COL5A1, it has been previously reported that type V collagen can assemble heterotypic fibers with type I collagen members [26]. However, the detailed pathogenesis and mechanism of COL5A1 are still unclear [27,28]. In recent years, various molecular biomarkers and genetic events have been used for classification and prognosis, which has continuously improved the accuracy of brain cancer treatment [29].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to COL5A1, it has been previously reported that type V collagen can assemble heterotypic fibers with type I collagen members [26]. However, the detailed pathogenesis and mechanism of COL5A1 are still unclear [27,28]. In recent years, various molecular biomarkers and genetic events have been used for classification and prognosis, which has continuously improved the accuracy of brain cancer treatment [29].…”
Section: Discussionmentioning
confidence: 99%
“…Two individuals with pathogenic COL5A1 variants and one with a COL5A1 VUS had vascular complications. Severe vascular complications have been reported in another 16 and two probands with (likely) pathogenic variants in COL5A1 and COL5A2 , respectively (Angwin et al, 2020; Borck et al, 2010; Karaa & Stoler, 2013; Mehta et al, 2012; Monroe et al, 2015; Richer et al, 2020; Weerakkody et al, 2018; Yasuda et al, 2013; Ziganshin et al, 2015) (Table ). Remarkably, 10 COL5A1 variants and both COL5A2 variants concerned a glycine substitution.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, 10 COL5A1 variants and both COL5A2 variants concerned a glycine substitution. Recently, four probands with multifocal fibromuscular dysplasia and varying, but generally mild manifestations of cEDS were described who harbored the same COL5A1 c.1540G>A, p.(Gly514Ser) variant (Richer et al, 2020). Notably, our patient harboring the COL5A1 VUS c.1477G>A, p.(Gly493Arg), located in the same region, had a hepatic and external iliac artery dissection and several pseudoaneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both the MMP2 expression level in myocardial tissue and blood circulation was most frequently reported to represent myocardial remodeling accompanied by myofibrosis, inflammation, and consequent development of heart failure (George et al, 2005;Andreasová et al, 2020). It has been reported that COL5A1 mutations are closely related to the abnormal heart or arterial development (Weerakkody et al, 2016;Richer et al, 2020). Ramirez et al (2012) identified that the expression level of COL5A1, reflecting the status of inflammatory and extracellular adhesion, was increased in left ventricle tissues in relation to the hypoxia response.…”
Section: Discussionmentioning
confidence: 99%